The Origins and Early Evolution of the ASMS and Craniomaxillofacial Surgery: A Surgical Discipline in Its Infancy. Issue 2 (June 2022) - Jarrahy, Reza; Kawamoto, Henry K.
As surgeons, in order to appreciate the possibilities of the future we must look back at our past. In honor of the 75th anniversary of the American Society of Maxillofacial Surgeons (ASMS), this historical article—the first in a series of 3 papers looking at the history of the ASMS and the evolution of craniomaxillofacial surgery as a distinct surgical subspecialty—reviews key figures and events that are germane to the development of our field from 1947, when the ASMS was founded, to 1971.